2019
DOI: 10.1007/978-3-030-36412-0_35
|View full text |Cite
|
Sign up to set email alerts
|

On Vertex-Edge and Independent Vertex-Edge Domination

Abstract: Given a graph G = (V, E), a vertex u ∈ V ve-dominates all edges incident to any vertex of NG [u]. A set S ⊆ V is a ve-dominating set if for all edges e ∈ E, there exists a vertex u ∈ S such that u vedominates e. Lewis [Ph.D. thesis, 2007] proposed a linear time algorithm for ve-domination problem for trees. In this paper, first we have constructed an example where the proposed algorithm fails. Then we have proposed a linear time algorithm for ve-domination problem in block graphs, which is a superclass of tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Finding even in cubic planar graphs is NP-hard [6]. The vertex-edge domination problem can be solved in linear time on block graphs [7]. In the same paper it is also shown that finding in undirected path graphs is NP-complete.…”
Section: Related Workmentioning
confidence: 98%
“…Finding even in cubic planar graphs is NP-hard [6]. The vertex-edge domination problem can be solved in linear time on block graphs [7]. In the same paper it is also shown that finding in undirected path graphs is NP-complete.…”
Section: Related Workmentioning
confidence: 98%
“…Approximation algorithm and approximation hardness results are proved in [14]. In [16], the authors designed a linear-time algorithm for the ve-domination problem in block graphs and showed that this problem remains NP-complete for undirected path graphs. Recently, Jena and Das [9] have studied the ve-domination problem in unit disk graphs.…”
Section: Introductionmentioning
confidence: 99%